1990
DOI: 10.2307/2579617
|View full text |Cite
|
Sign up to set email alerts
|

Public Beliefs about the Causes of Homelessness

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Oxford University Press is collaborating with JSTOR to digitize, preserve and extend access to Social Forces. AbstractUsing data from a survey of Nashville, Tennessee, residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 4 publications
2
66
0
Order By: Relevance
“…Effects found for education appear in conflict with those of Lee, Jones, and Lewis (1990) and Phelan et al (1995). It appears possible that respondents at higher levels of education may have expected that homeless individuals shared the same opportunities for advancement that they had, decreasing their awareness of possible structural or societal influences that may have contributed to an individual's becoming homeless.…”
Section: Predictors Of Attitudes On Homelessnessmentioning
confidence: 87%
See 1 more Smart Citation
“…Effects found for education appear in conflict with those of Lee, Jones, and Lewis (1990) and Phelan et al (1995). It appears possible that respondents at higher levels of education may have expected that homeless individuals shared the same opportunities for advancement that they had, decreasing their awareness of possible structural or societal influences that may have contributed to an individual's becoming homeless.…”
Section: Predictors Of Attitudes On Homelessnessmentioning
confidence: 87%
“…Toro and McDonell (1992) found that younger and female respondents were more generally sympathetic regarding the homeless population, and were more aware of related structural factors. Examining effects of education, Phelan, Link, Stueve, and Moore (1995) found that better educated respondents expressed greater tolerance for homeless people, but less support for economic aid for them, while Lee, Jones, and Lewis (1990) noted that increased education predicted less support for a personal deficiency model of homelessness. Studies have also examined the effects of political party allegiance and income on attitudes towards homelessness, with varying results (Furnham, 1996;Toro & McDonell, 1992).…”
Section: Demographic Predictorsmentioning
confidence: 99%
“…Most studies were conducted in western societies (Shek & Ma, 2008) and input is needed from non-western countries to enhance our understanding of adolescents' view of poverty. We would also point out that most attribution of poverty studies used the term poverty generically (Furnham, 1982;Harper, 2003;Lee, Jones, & Lewis, 1990;Wilson, 1996). Since the poor fall into different categories (such as the homeless, the elderly, single parents, the rural poor and many more), there is a possibility that different respondents call up different images of the poor when responding to an attribution questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…A. Lee, Jones, & Lewis, 1990). Common negative attitudes toward homelessness may be associated with the perceptions that homeless people panhandle (B.…”
Section: Attitudes Toward the Homeless Young And The Homeless Oldmentioning
confidence: 99%